Analysis of Personality Factors’ in Second Language Acquisition: (A Survey of Fifth Semester Students’ of English Education Study Program at UIN SMDD Bukittinggi) - Febriana, Febriana; Reflinda, Reflinda; Roza, Veni; Melani, Melyann (Pusdikra-Publishing.com, 2024)
This research was carried out based on problems encountered by researcher in the fifth semester of the English language education study program at UIN SMDD Bukittinggi. First, many students do not yet recognize their personalities. Second, students still feel insecure, anxious and afraid in using their second language skills because of their personality. The aim of this research is to describe student personality which has an impact on the process of second language acquisition for students in the fifth semester and to describe how personality factors influence the second language acquisition of students in the fifth semester. This research is research with a mixed approach. The instruments of this research are questionnaires and interviews. The respondents for this research for quantitative data were 46 fifth semester students of the English language education study program. The informants for this research were 4 students who had participated and filled out the research questionnaire. Data was obtained from three classes through distributing questionnaire instruments and interviews with fifth semester students. There are two data analyzes in this research, namely descriptive statistical data analysis for quantitative data and qualitative data analysis for researcher using the theory of Miles and Huberman in Sugiyono. The findings and discussion outline the answers to the three research questions, namely students' personality types, students' level of second language acquisition, and the relationship between personality and second language acquisition. First, it was found that the personality types of fifth semester students are conscientiousness, extroversion and its opposite, neuroticism, and agreeableness. Second, more than half of the fifth semester English education students have reached the level of continuous language development/advanced fluency with 57.6%. Third, students have the view that personality can facilitate or complicate the process of language acquisition, but it can still be influenced by other factors such as one's desire and self-control.